2020
DOI: 10.3390/w12123561
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as an Eco-Friendly and Economical Adsorbent for the Removal of Colorants (Dyes) from Aqueous Environment: A Review

Abstract: Dyes (colorants) are used in many industrial applications, and effluents of several industries contain toxic dyes. Dyes exhibit toxicity to humans, aquatic organisms, and the environment. Therefore, dyes containing wastewater must be properly treated before discharging to the surrounding water bodies. Among several water treatment technologies, adsorption is the most preferred technique to sequester dyes from water bodies. Many studies have reported the removal of dyes from wastewater using biochar produced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(59 citation statements)
references
References 141 publications
(179 reference statements)
0
57
0
2
Order By: Relevance
“…The process of biochar adsorption mainly depends on pyrolysis conditions, surface functional properties, feedstock forms, and biochar porosity [39]. Several studies have reported on the adsorption of inorganic and organic pollutants from aqueous solutions using biochars [21,40]. They have investigated the impact of several factors such as pyrolysis temperature and solution pH on the adsorption process [41].…”
Section: Introductionmentioning
confidence: 99%
“…The process of biochar adsorption mainly depends on pyrolysis conditions, surface functional properties, feedstock forms, and biochar porosity [39]. Several studies have reported on the adsorption of inorganic and organic pollutants from aqueous solutions using biochars [21,40]. They have investigated the impact of several factors such as pyrolysis temperature and solution pH on the adsorption process [41].…”
Section: Introductionmentioning
confidence: 99%
“…131 Methyl orange (MO), methylene blue (MB), reactive yellow 145, malachite green (MG), methyl violet (MV), organic dye sunset yellow (SY), alizarin yellow, and Congo red are some common dyes that have harmful effects on the environment and human beings when disposed into water bodies. 132 Thus, the adsorption of these dyes by magnetic chitosan adsorbents will reduce their adverse effects in the community. The adsorption of MO onto magnetic chitosan beads (MagCH) was conducted and the influence of pH in the system was investigated.…”
Section: Magnetic Chitosan Adsorbents For Dyesmentioning
confidence: 99%
“…Several studies found that activated bio-char sorption technologies are highly efficient and economical as compared to conventional methods for contaminant removal or wastewater treatment [66][67][68][69]. Other water treatment technologies have several limitations as compared to activated bio-char.…”
Section: 32345051]mentioning
confidence: 99%